Practice, preference and performance of cattle under peri-urban dairy management system in Mymensingh - Siddiquee, NU; Rahman, SMA; Bhuiyan, MSA; Rahman, AKMA; Amin, MR; Bhuiyan, AKFH (Bangladesh Journal of Animal Science, 2013)
<!--[if gte mso 9]> <![endif]--><span style="font-size: 8.5pt; line-height: 115%; font-family: "Calibri","sans-serif"; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: "Times New Roman"; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;">The objective of this research was <span style="font-size: 8.5pt; line-height: 115%; font-family: "Calibri","sans-serif"; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: "Times New Roman"; mso-fareast-theme-font: minor-fareast; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: Calibri; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">to assess the status of cattle in respect of breeding system, quality of breeding services, their production, reproduction, health status, management system and marketing system using an in-depth baseline survey. <span style="font-size: 8.5pt; line-height: 115%; font-family: "Calibri","sans-serif"; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: "Times New Roman"; mso-fareast-theme-font: minor-fareast; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: Calibri; mso-bidi-theme-font: minor-latin; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">The mean of homestead land owned by the farmers was 36.17± 32.94 decimal and most of them (48.3%) own very low homestead land (11-50 decimal). Average cultivable land owned was found as 101.52±61.044 decimal and a considerable number of farmers have medium (51-150 decimal) to high (151 onward decimal) land area. From the collected data, it is clear that most of the households have cattle and chicken. But among cattle owners, about 77.62% have lower number (1-3). Most of the farmers 69.8% use locally available grass and only 3.2 % fed exotic grass to their cows. <span style="font-size: 8.5pt; line-height: 115%; font-family: "Calibri","sans-serif"; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: "Times New Roman"; mso-fareast-theme-font: minor-fareast; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: "Times New Roman"; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Milk sale and consumption (52.13<span style="font-size: 8.5pt; line-height: 115%; font-family: "Calibri","sans-serif"; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: "Times New Roman"; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">%) was found as main objective behind cattle rearing. <span style="font-size: 8.5pt; line-height: 115%; font-family: "Calibri","sans-serif"; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: "Times New Roman"; mso-fareast-theme-font: minor-fareast; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: Calibri; mso-bidi-theme-font: minor-latin; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Semi-intensive method of rearing was found most acceptable (77.62%) among the peri-urban farmers. Disease problem was quite high because of lack of routine vaccination where vaccination was found to be practiced by only 38.46% farmers. <span style="font-size: 8.5pt; line-height: 115%; font-family: "Calibri","sans-serif"; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: "Times New Roman"; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;">Indigenous cattle are of high preference among the farmers (52.45%) because of its easy management and high resistance to disease, 41.2%<span style="font-size: 8.5pt; line-height: 115%; font-family: "Calibri","sans-serif"; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: "Times New Roman"; mso-fareast-theme-font: minor-fareast; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: Calibri; mso-bidi-theme-font: minor-latin; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> percent farmers preferred crossbred cattle. Main reasons behind preference for Deshi cattle were easy management (24.48%) and lower feed requirement (12.59%) whereas, reason behind crossbred preference (35.66%) was higher milk production. Artificial Insemination (AI) was preferred (61.06%) over natural service (38.94%). For artificial insemination, semen of Holstein Friesian (43.07%) was preferred where Deshi was the second most choice (32.12%). Most of the farmers (82.9%) have no idea about genotype, quality & merit of semen. Average milk yield of Deshi and crossbred genotype were found as 1.72±0.80 and 6.65±5.05 liter per day respectively whereas lactation period and dry period were found respectively as 243.98±113.13 and 92.37±63.14 days in crossbred, 249.69±106.93 and 96.58±32.06 days in Deshi cows. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> <!--[endif] --> <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> DOI: http://dx.doi.org/10.3329/bjas.v42i2.18485 <span style="font-size: 11.0pt; line-height: 115%; font-family: "Calibri","sans-serif"; mso-fareast-font-family: Calibri; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;">Bang. J. Anim. Sci. 2013. 42 (2): 89-95<!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--><span style="font-size: 11.0pt; line-height: 115%; font-family: "Calibri","sans-serif"; mso-fareast-font-family: Calibri; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;">